Bladder and Bowel Management in Dogs With Spinal Cord Injury - Granger, Nicolas; Olby, Natasha J.; Nout-Lomas, Yvette S.; , The Canine Spinal Cord Injury Consortium (CANSORT-SCI); Moore, Sarah A.; Olby, Natasha J.; Levine, Jonathan M.; Lewis, Melissa J.; Jeffery, Nick D.; da Costa, Ronaldo Casimiro; Nout-Lomas, Yvette S.; Fenn, Joe; et al. (Frontiers in Veterinary Science, 2020)
Spinal cord injury in companion dogs can lead to urinary and faecal incontinence or retention, depending on the severity and localisation of the lesion along the canine nervous system. The bladder and gastrointestinal dysfunction caused by lesions of the autonomic system can be difficult to recognise, interpret and are easily overlooked. Nevertheless, it is crucial to maintain a high degree of awareness of the impact of micturition and defecation disturbances on the animal’s condition, welfare and on the owner. The management of these disabilities is all the more challenging that the autonomic nervous system physiology is a complex topic. In this review, we propose to briefly remind the reader the physiology of micturition and defecation in dogs. We then present the bladder and gastrointestinal clinical signs associated with sacral lesions (i.e. the L7-S3 spinal cord segments and nerves) and supra-sacral lesions (i.e. cranial to the L7 spinal cord segment), largely in the context of intervertebral disc herniation. We summarise what is known about the natural recovery of urinary and faecal continence in dogs after spinal cord injury. In particular we review the incidence of urinary tract infection after injury. We finally explore the past and recent literature describing management of urinary and faecal dysfunction in the acute and chronic phase of spinal cord injury. This comprises medical therapies but importantly a number of surgical options, some known for decades such as sacral nerve stimulation, that might spark some interest in the field of spinal cord injury in companion dogs.